The relationship between health-promoting behaviors and socio-demographic and clinical characteristics of patients with diabetes mellitus - GÜLSEVEN KARABACAK, BİLGİ (My University, 2022)
Objective: In this study, it was aimed to investigate the relationship between health-promoting attitudes and socio-demographic and the clinical characteristics of patients with diabetes. Methods: The study sample comprised a total of 267 patients with diabetes mellitus aged 18 years and older, who had previously been diagnosed as Type 1 or Type 2 diabetes mellitus for at least 6 months, who had no gestational diabetes mellitus and who had presented to the Internal Diseases Outpatient Clinic in Kocaeli between June-September 2015. Collection of the data were realized by the researchers through face-to-face interviews using the “Patient Information Form” and the “Health-Promoting Lifestyle Profile-II”. The validity-reliability study of the scale for the Turkish population was carried out by Bahar et al. The scale comprises six factors including health responsibility, physical activity, nutrition, spiritual growth, interpersonal relations and stress management. Results: The patients scored highest in the interpersonal relations and scored lowest in the physical activity factors. Patients who were aged between 18-44 years, those who were high school graduates, those who were retired, those who had a well-balanced income and those with no additional chronic disease had higher scores in Health-Promoting Lifestyle Profile-II compared to others. We found that the healthpromoting attitudes were not affected by the duration of diabetes mellitus, body mass index or the presence of diabetes in the family. Conclusion: We determined that healthy lifestyle attitudes were demonstrated moderately by the patients with diabetes mellitus, and these attitudes were found to be associated with socio-demographic and clinical variables such as patient’s age, education status, diabetes type and
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Tıbbi Ekoloji ve Hidroklimatoloji; Medicine; Health Sciences; Internal Medicine Sciences; Medical Ecology and Hydroclimatology; TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); Araştırma ve Teori; İncelemeler ve Referanslar (tıbbi); Research and Theory; Reviews and References (medical); Demographic factors; disease attributes; diabetes mellitus; health promotion; nurse; LIFE-STYLE; RISK